Infants with HIV-AIDS Mothers (BIHA): A Case Report - Bunga Sherley Aprilia; Ity Sulawati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
HIV (Human Immunodeficiency Virus) is an RNA class retrovirus that specifically attacks the human immune system. A decrease in the immune system in HIV-infected people facilitates various infections, which can lead to the onset of AIDS. AIDS (Acquired Immunodeficiency Syndrome) is a set of clinical symptoms and signs in people with HIV due to opportunistic infections due to a decrease in the immune system. Opportunistic infections can be caused by various viruses, fungi, bacteria, and parasites, and can attack various organs, including the skin, gastrointestinal tract / intestines, lungs, and brain. Infection of infants or children by HIV (Human Immunodeficiency Virus) is mostly transmitted vertically from mother to baby during pregnancy, childbirth, and through breast milk. Horizontal transmission through transfusion of blood products or other transmission such as child sexual abuse occurs less frequently than vertical transmission. A newborn baby from a mother with HIV-AIDS, accompanied by signs of infection in the baby, the patient's mother was found to be reactive on the HIV test and a decrease in CD4. Physical examination results on system examination were good. The results of laboratory support examinations obtained an increase in CRP and hypoglycemia. The diagnosis of infant with mother HIV-AIDS (BIHA) and neonatal infection was established based on the history, physical examination results and supporting examinations of the mother and baby that had been carried out. The patient received main therapy by giving antiretroviral prophylaxis in the form of zidovudine 4mg/kg/time, 2 times a day until the baby is 6 weeks old and antibiotics according to the diagnosis.